THE APPLICATION OF VALUE ENGINEERING IN SOIL IMPROVEMENT (PROJECT OF PELINDO III TELUK LAMONG SURABAYA) - Boy, Wendi; Wibowo, Muhammad Agung; Huda, Miftahul (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2020)
This study was conducted on soil improvement works development Pelabuhan Indonesia III projects, Teluk Lamong Surabaya. The aim of the study was to obtain the optimization of the acceleration of soil consolidation using preloading with prefabrication vertical drain (PVD) and prefabrication horizontal drain (PHD). The method used in this study is the optimization of value engineering methods, which generally consists of phases: information, creativity, analysis, development and recommendation. The study concluded that the consolidation of the soil with alternative preloading system using landfill with gd = 1.91 kg/m3 and using PVD/PHD brand Geowork type MW- 408/Geowork type SD 100 X 20 with a distance of 80 cm is a method the most optimal soil improvement. This alternative produces a faster consolidation of 53 days from the scheduled time and cost savings of about Rp 1.77 billion from the planned start-up costs.